Клинические аспекты применения стекловолоконной армирующей системы в реставрации зубов, подвергнутых эндодонтическому лечению (Эндодонтия Today, 2020)
Results of clinical application of a fiberglass reinforced tape in direct composite restorations for non-vital teeth with hard tissue defects give reason to recommend Armosplint as a promising material for clinical dentistry.